Посмертные изменения зрелых цистицеркоидов карликового цепня в ворсинках тонкого кишечника белых мышей - Мирецкий, О.Я.; Пашкова, В.С. (Вестник зоологии, 1967)
Histological study of dead mature cystocercoids in small intestines fibres of albino mice, whom for invasion intensity increase cortyson was administrated to, enabled one to describe successive stages of the dead cystocercoid destruction — structure obliteration, diminution of cystercoid heads with the appearance of oedematous liquid, resolution of cell detrit with the origin of a cyst.